Улучшенные оценки точности разностной схемы для двумерного параболического уравнения с учетом эффекта от краевых и начальных условий - Майко, Н.В. (Кибернетика и системный анализ, 2017)
Отримано покращені оцінки точності скінченно-різницевих апроксимацій першої крайової задачі для двовимірного рівняння теплопровідності з урахуванням впливу початкових і крайових умов. Показано, що точність схеми вища поблизу бічних граней і дна просторово-часового паралелепіпеда. We obtain the improved error estimates of the finite-difference scheme for a two-dimensional parabolic equation in a unit square, considering the effect of the Dirichlet boundary condition and the initial condition. We prove that the accuracy order is higher near the sides and the bottom of the space-time parallelepiped.